Improved detection of paroxysmal atrial fibrillation using a semi-supervised model based on ECG signals - Artal Gracia, Sara; Martínez Cortés, Juan Pablo; Miguel Artiaga, Antonio; Ramírez García, Julia (Jornada de Jóvenes Investigadores del I3A, 2024)
The aim of this work is to evaluate whether a semi-supervised learning model improves the performance of a supervised one in the diagnosis of paroxysmal atrial fibrillation, a task in which training data are scarce and the proportion of cases is unbalanced.